Russian exports by regional origin: disparities, diversity and decentralization in the transformation process - Rolf J. Langhammer; Matthias Lücke (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1992)
This paper analyses the contribution of 71 regional entities to the exports of the Russian Federation outside the Soviet Union in 1989. A distinction is made between export earnings in convertible and nonconvertible currency, as well as between four major commodity categories. The focus of the analysis is on the likely consequences of greater regional economic autonomy within Russia. It is found that only very few areas would clearly benefit from enhanced regional control over export earnings, mainly by obtaining a higher share of resource rents. Furthermore, in the present environment of distorted prices and balance of payments constraints, decentralization could lead to substantial windfall gains for established exporters at the expense of areas that happen to supply mainly the domestic market. The speedy introduction of a price structure reflecting genuine scarcities would therefore help not only to eliminate allocative inefficiency, but also to minimize interregional distributional conflicts.
Keywords: 330; Regionaler Außenhandel; Russland